2016
DOI: 10.1126/science.aac7125
|View full text |Cite
|
Sign up to set email alerts
|

Climate change disables coral bleaching protection on the Great Barrier Reef

Abstract: Coral bleaching events threaten the sustainability of the Great Barrier Reef (GBR). Here we show that bleaching events of the past three decades have been mitigated by induced thermal tolerance of reef-building corals, and this protective mechanism is likely to be lost under near-future climate change scenarios. We show that 75% of past thermal stress events have been characterized by a temperature trajectory that subjects corals to a protective, sub-bleaching stress, before reaching temperatures that cause bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
355
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 413 publications
(385 citation statements)
references
References 22 publications
8
355
1
4
Order By: Relevance
“…This increases population fitness in the short term, but may decrease it in the long term. Such a situation may be observed on the Great Barrier Reef when protective pulses of short-term, warm water occur before bleaching events (Ainsworth et al, 2016).…”
Section: Evolution In the Face Of Environmental Changementioning
confidence: 99%
“…This increases population fitness in the short term, but may decrease it in the long term. Such a situation may be observed on the Great Barrier Reef when protective pulses of short-term, warm water occur before bleaching events (Ainsworth et al, 2016).…”
Section: Evolution In the Face Of Environmental Changementioning
confidence: 99%
“…On the Great Barrier Reef (GBR), mean summer maximum temperatures have been reported to have nearly 2 • C difference at reefs 250 km apart (South Molle Island to Magnetic Island; Howells et al, 2013). Different thermal histories on the GBR have been found to influence bleaching susceptibility (Ulstrup et al, 2006;Ainsworth et al, 2016) and the physiological performance of a generalist coral symbiont (Howells et al, 2012). Warmer latitudes have also been shown to enhance heritable thermal tolerance, up to 10-fold in Acropora millepora from the GBR (Dixon et al, 2015).…”
Section: Broad Temperature Gradientsmentioning
confidence: 99%
“…It has been shown that corals transplanted into warmer waters are able to better respond to acute heat stress than colonies that remain in cooler waters (Palumbi et al, 2014). Indeed, pre-exposure to a mild thermal stress is likely to initiate an acclimation mechanism protecting corals from bleaching in several recent heat stress events (Ainsworth et al, 2016). Despite this ecological and physiological evidence for acclimation, little is known about the molecular mechanisms underlying this type of response.…”
Section: Acclimations By Epigenetic Modifications In Cnidariamentioning
confidence: 99%